2011
DOI: 10.1177/1545109711401750
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lipodystrophy and Dyslipidemia among Patients with HIV Infection on Generic ART in Rural South India

Abstract: As antiretroviral therapy (ART) becomes more available to the HIV-infected population, it is important to determine the prevalence of its long-term complications. In this cross-sectional study, 145 HIV-positive patients on ART, 146 HIV-positive patients not on ART, and 72 HIV-negative individuals visiting the Namakkal District Head Quarters Hospital, Tamil Nadu, India, were recruited from February 2007 to April 2009. Among the patients on ART, the prevalence of lipodystrophy was 60.7%; 22.7% with lipohypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
4

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 23 publications
6
32
4
Order By: Relevance
“…In our study lipodystrophy was observed in 33.7%. Few studies on stavudine based HAART have reported a prevalence between 27% -60.7 % ( 8,22,28,29,30,(33)(34) . We found lipoatrophy as the commonest subtype similar to others (8,11,12,20,21,33,34) whereas Aurpibul et al (22) reported lipohypertrophy as the commonest subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study lipodystrophy was observed in 33.7%. Few studies on stavudine based HAART have reported a prevalence between 27% -60.7 % ( 8,22,28,29,30,(33)(34) . We found lipoatrophy as the commonest subtype similar to others (8,11,12,20,21,33,34) whereas Aurpibul et al (22) reported lipohypertrophy as the commonest subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for this syndrome remains unclear. It has been proposed that antiretroviral drugs such as protease inhibitors (PI) and/ or nucleoside analogues (stavudine) could contribute to the development of such clinical and metabolic abnormalities (2,6,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(28)(29)(30)(31)(32)(33)(34)(35) . Various risk factors have been found to be associated with the development of lipodystrophy like older age and increasing duration of treatment (22,33,34,35) .…”
mentioning
confidence: 99%
“…The association between dyslipidemia and HAART has been mainly described for PIs based regimens (Anastos et al, 2007;Nery et al, 2011). Lipid derangements were higher among patients who received d4T when compared with other NRTIs (Kalyanasundaram et al, 2012;Ceccato et al, 2011). NNRTIs derange lipid profiles during therapy (Van der Valk et al, 2001;Young et al, 2005); however, evidences in support of the characterization of dyslipidemia regarding NNRTIs after HAART switching in sub-Saharan African countries are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Lipodystrophy was observed in nearly one patient treated for three, and more than half of the cases were the atrophic form. Others have made the same observation emphasizing the determining role of stavudine which was widely used in most national programs in developing countries [5] [7] [11]. The impact of ART on the occurrence of metabolic syndrome is due to the mechanism of action of ARVs Drugs which determine dysfunction of lipid and glucose metabolism of patients [12]- [15].…”
Section: Discussionmentioning
confidence: 99%